Inklusi Sosial dalam Program Kartu Jakarta Sehat (KJS) dan Kartu Jakarta Pintar (KJP) di DKI Jakarta - Ruman, Yustinus Suhardi (Bina Nusantara University, 2014)
Article focuses on elaborating social inclusion in health and education policy in DKI Jakarta through Kartu Jakarta Sehat and Kartu Jakarta Pintar program. The program is composed by the governor and vice governor of DKI Jakarta, Joko Widodo and Basuki Tjahaja Purnama. By using interpretative method, secondary data and social exclusion and inclusion concept, this article shows that Kartu Jakarta Sehat and Kartu Jakarta Pintar program can be valued as social inclusion program. Through Kartu Jakarta Pintar program everyone who is the citizen of DKI Jakarta can participate in basic education; and through Kartu Jakarta Sehat all citizens of DKI Jakarta get merely health services. The policies make education and health services more open for all people. Participation in education and getting health services are the rights of all people. These rights were acknowledged by international community through International Convension about economic, social and cultural rights in 1966. This convention was ratified by the Indonesian Government through Law Number 11, 2005. So the normative basis of Kartu Jakarta Sehat and Kartu Jakarta Pintar Program is identified as inclusion policy in accordance with the expectation of international community and also is appropriate with the Law of Indonesia.